Use of regional analgesia and risk of delirium in older adults with multiple rib fractures: An Eastern Association for the Surgery of Trauma multicenter study. Issue 2 (August 2021) - O'Connell, Kathleen M.; Patel, Kushang V.; Powelson, Elisabeth; Robinson, Bryce R.H.; Boyle, Kelly; Peschman, Jacob; Blocher-Smith, Ethan C.; Jacobson, Lewis; Leavitt, Justin; McCrum, Marta L.; Ballou, Jessica; Brasel, Karen J.; et al.
Abstract : BACKGROUND: Single-center data demonstrates that regional analgesia (RA) techniques are associated with reduced risk of delirium in older patients with multiple rib fractures. We hypothesized that a similar effect between RA and delirium would be identified in a larger cohort of patients from multiple level I trauma centers. METHODS: Retrospective data from seven level I trauma centers were collected for intensive care unit (ICU) patients 65 years or older with ≥3 rib fractures from January 2012 to December 2016. Those with a head and/or spine injury Abbreviated Injury Scale (AIS) score of ≥ 3 or a history of dementia were excluded. Delirium was defined as one positive Confusion Assessment Method for the Intensive Care Unit score in the first 7 days of ICU care. Poisson regression with robust standard errors was used to determine the association of RA (thoracic epidural or paravertebral catheter) with delirium incidence. RESULTS: Data of 574 patients with a median age of 75 years (interquartile range [IQR], 69–83), Injury Severity Score of 14 (IQR, 11–18), and ICU length of stay of 3 days (IQR, 2–6 days) were analyzed. Among the patients, 38.9% were women, 15.3% were non-White, and 31.4% required a chest tube. Regional analgesia was used in 19.3% patients. Patient characteristics did not differ by RA use; however, patients with RA had more severe chest injury (chest AIS, flail segment, hemopneumothorax, thoracostomy tube). In univariate analysis, there was no difference in the likelihood of delirium between the RA and no RA groups (18.9% vs. 23.8% p = 0.28). After adjusting for age, sex, Injury Severity Score, maximum chest AIS, thoracostomy tube, ICU length of stay, and trauma center, RA was associated with reduced risk of delirium (incident rate ratio [IRR], 0.65; 95% confidence interval [CI], 0.44–0.94) but not with in-hospital mortality (IRR, 0.42; 95% CI, 0.14–1.26) or respiratory complications (IRR, 0.70; 95% CI, 0.42–1.16). CONCLUSION: In this multicenter cohort of injured older adults with multiple rib fractures, RA use was associated with a 35% lower risk of delirium. Further studies are needed to standardize protocols for optimal pain management and prevention of delirium in older adults with severe thoracic injury. LEVEL OF EVIDENCE: Therapeutic, level IV; Epidemiologic, level III. Abstract : Supplemental digital content is available in the text.